Актуальні аспекти управління капіталом комерційного банку - Зінковська, Я.В. (Культура народов Причерноморья, 2013)
У статті дано визначення поняття «управління капіталом банку». Розглянуто механізм
управління капіталом банку та його складові. Проведено аналіз вартості, структури та достатності
власного капіталу ПАТ КБ «ПриватБанк». Визначено ефективність управління капіталом з
використанням нормативів НБУ. Представлені основні принципи та напрямки ефективного управління
капіталом банку на прикладі ПАТ КБ «ПриватБанк».
Ключові слова: капітал банку, управління капіталом банку, економічні нормативи діяльності банків,
показники ефективності управління капіталом. В статье дано определение понятия «управление капиталом банка». Рассмотрен механизм
управления капиталом банка и его составляющие. Проведен анализ стоимости, структуры и
достаточности собственного капитала ПАО КБ «ПриватБанк». Определена эффективность
управления капиталом с использованием нормативов НБУ. Представлены основные принципы и
направления эффективного управления капиталом банка на примере ПАО КБ «ПриватБанк».
Ключевые слова: капитал банка, управление капиталом банка, экономические нормативы
достаточности капитала банка, показатели эффективности управления капиталом. The article provides a definitions of such notion as management of the bank's capital. It considers a
management mechanism by the bank's capital and it's constituents: subjects of management mechanism of the
bank's capital, object of management mechanism of the bank's capital and management process of the bank's
capital, that embraces such elements as management methods and management instruments. Management
process by the bank's capital on macroeconomic and microeconomic levels has been considered. PJSC CB
"PrivatBank" was acknowledged as the leading bank in Ukraine at all criteria. That is why the analysis of cost
and sufficientness on an example of the capital of PJSC CB "PrivatBank" have been performed. The analysis on
the methodology of corresponding organs that conduct a bank supervision and conduct control in the field of
bank activity, namely on the norms of National Bank of Ukraine, and also questions of estimation of structure
and dynamics of capital of PJSC CB "PrivatBank" for 2010-2012 have been performed. Basic principles and
direction of effective management the capital of bank on the example of PJSC CB "PrivatBank" have been
indicated in the article.
Keywords: bank's capital, management by the capital of bank, economic norms of sufficientness of capital of
bank, indexes of management efficiency by a capital.